Idher Bumi as Traditional Ceremony in Banyuwangi: from Religion to Cultural Tourism - Dinna Eka Graha Lestari (International Journal of Social Science and Religion (IJSSR), 2020)
The influence of modernization, cultural value of a society that changes towards cultural values. Society can be classified as a modern society because it reflects the cultural characteristics of modern society. The traditional IdherBumi ceremony can provide a large income for the village. Revenue comes from parking tickets, sponsorships and also local governments. Based on the situation and conditions in the field, the focus of this research is: (1) The concept of the IdherBumi Traditional Ceremony in the Using Community, (2) The Change in the Traditional IdherBumi Ceremony of the Using Community, (3). Related to the above focus, the approach used in this research is descriptive qualitative case study method, and uses data validity techniques that are based on trust, transformational, dependability and certainty based on objectivity.